Recent Trends in Prostate Cancer Incidence by Age, Cancer Stage, and Grade, the United States, 2001–2007 - Jun Li; Joseph A. Djenaba; Ashwini Soman; Sun Hee Rim; Viraj A. Master (Prostate Cancer)
Objective. To examine prostate cancer trends by demographic and tumor characteristics because a comprehensive examination of recent prostate cancer incidence rates is lacking. Patients and Methods. We described prostate cancer incidence rates and trends using the 2001–2007 National Program of Cancer Registries and Surveillance, Epidemiology, and End Results Program data (representing over 93% of US population). Because of coding changes in cancer grade, we restricted analysis to 2004–2007. We conducted descriptive and trend analyses using SEER*Stat. Results. The overall prostate cancer incidence rate was stable from 2001 to 2007; however, rates significantly increased among men aged 40–49 years (APC = 3.0) and decreased among men aged 70–79 years (APC = 2.3), and 80 years or older (APC = −4.4). About 42% of localized prostate cancers diagnosed from 2004 to 2007 were poorly differentiated. The incidence of poorly differentiated cancer significantly increased among localized (APC = 8.0) and regional stage (APC = 6.1) prostate cancers during 2004–2007. Conclusions. The recent trend in prostate cancer incidence was stable but varied dramatically by age. Given the large proportion of poorly differentiated disease among localized prostate cancers and its increasing trend in more recent years, continued monitoring of prostate cancer incidence and trends by demographic and tumor characteristics is warranted.